Formulation Study of Acetosal Suppositories Using PEG 400 and PEG 6000: Impact on Physical Properties - Dewi Rashati; Dinar Rizqika Fauza; Mikhania Christiningtyas Eryani; Asa Falahi; Anies Rohman (MEDFARM: Jurnal Farmasi dan Kesehatan, 2026)
Acetosal suppositories are rectal dosage forms that can be used as an alternative route of administration to minimize gastrointestinal irritation associated with oral acetosal therapy. The suppository base plays an important role in determining the physical characteristics of the preparation. The objective of this study was to evaluate how varying concentrations of polyethylene glycol (PEG) 400 and PEG 6000 affect the physical properties of acetosal suppository formulations. Three formulations were prepared using PEG 400:PEG 6000 ratios of F1 (3:7), F2 (1:1), and F3 (7:3). Physical evaluations included organoleptic properties, weight uniformity, melting time, melting point, and hardness. All formulations exhibited similar organoleptic characteristics, namely solid shape, pale white color, and characteristic odor. The average weight uniformity values were 2594.3 ± 61.9 mg (F1), 2526.9 ± 83.1 mg (F2), and 2315.7 ± 45.4 mg (F3), with significant differences among formulations (p<0.05). The average melting times were 25.1 ± 0.981 min, 19.5 ± 0.574 min, and 15.9 ± 0.508 min for F1, F2, and F3, respectively (p<0.05). The average melting points were 36.3 ± 0.577°C, 35.7 ± 0.577°C, and 34.3 ± 0.577°C for F1, F2, and F3, respectively (p=0.014). Hardness values were 1.93 ± 0.115 kg (F1), 1.87 ± 0.115 kg (F2), and 1.53 ± 0.115 kg (F3), with significant differences among formulations (p<0,05). In conclusion, variations in PEG 400 and PEG 6000 concentrations significantly affected weight uniformity, melting time, melting point, and hardness, while organoleptic properties remained unchanged. Formulations F1 and F2 fulfilled all physical quality requirements and were considered optimal. Keywords: Acetosal, suppositories, PEG 400, PEG 6000